Balancing sustainability goals and treatment efficacy for PFAS removal from water - Md. Moshiur Rahman Tushar; Zaki Alam Pushan; Nirupam Aich; Lewis S. Rowles (npj Clean Water)
Abstract Per- and polyfluoroalkyl substances (PFAS) are emerging water contaminants with significant environmental and health impacts, posing challenges in water treatment due to their high stability and persistence. With increasing regulations, a critical need remains in understanding the sustainability of PFAS treatment technologies. Our review examines the environmental, economic, and social impacts of current PFAS treatment technologies across different water types and contexts. Additionally, we propose a framework for future sustainability studies to enable more holistic technology evaluations under specific conditions.